2021
DOI: 10.1002/mgg3.1590
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel SUOX pathogenic variants as the cause of isolated sulfite oxidase deficiency in a Chinese pedigree

Abstract: Background Isolated sulfite oxidase deficiency (ISOD) is a life‐threatening rare autosomal recessive disorder caused by pathogenic variants in SUOX (OMIM 606887) gene. The aim of our study was to establish a comprehensive genetic diagnosis strategy for the pathogenicity analysis of the SUOX gene within a limited time and to lay the foundation for precise genetic counseling, prenatal diagnosis, and preimplantation genetic diagnosis. Methods Two offspring from one set of parents were studied. Next‐generation seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…30 Recently, Du et al, two offspring identi ed with a heterozygous nonsense pathogenic variant (c.1200C>G, p.Y400*) and a heterozygous duplication (c.1549_1574dup, p.I525 Mfs*102) in the SUOX gene in the proband. 27 Lastly, Zhao et al, reported a Chinese new born patient presented with homocysteine and uric acid in plasma, cysteine and total homocysteine in the blood and S-sulfocysteine was abnormally elevated in urine. 28 The proband was manifested with progressive encephalopathy, tonic seizures, abnormal muscle tone, di culties in feeding, progressive neuropathological ndings, intermittent convulsions and axial dystonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Recently, Du et al, two offspring identi ed with a heterozygous nonsense pathogenic variant (c.1200C>G, p.Y400*) and a heterozygous duplication (c.1549_1574dup, p.I525 Mfs*102) in the SUOX gene in the proband. 27 Lastly, Zhao et al, reported a Chinese new born patient presented with homocysteine and uric acid in plasma, cysteine and total homocysteine in the blood and S-sulfocysteine was abnormally elevated in urine. 28 The proband was manifested with progressive encephalopathy, tonic seizures, abnormal muscle tone, di culties in feeding, progressive neuropathological ndings, intermittent convulsions and axial dystonia.…”
Section: Discussionmentioning
confidence: 99%
“…Among 32 reported variants, 20 variants are missense, 4 variants are nonsense, 6 variants are deletion which result into frameshift and one duplication. 4,[9][10][11][12][13][14][15][16][17][18][19][20]27,28 One deletion leads to loss of the wild type stop codon and followed by formation of a prolonged protein (Table 6). 13 ISOD is a very rare and extremely heterogenous disorder in terms of both genotype and phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inborn error arises from either mutations of SO protein (so‐called isolated SO deficiency (ISOD)) or inability to correct synthesis the pyranopterindithiolate cofactor (so‐called Moco deficiency (MoCD)) in vivo, resulting in the accumulation of excess toxic sulfite in serum [84–86] . Both ISOD and Moco deficiencies have been reported in several patients [87–91] . In 1967, Mudd et al., first reported the ISOD and then it is known as a rare autosomal recessive disorder in human [92] …”
Section: Oxidation Of Sulfitementioning
confidence: 99%
“…The incidence of ISOD has not been reported epidemiologically. To date, < 50 cases have been reported worldwide (van der Klei-van Moorsel et al, 1991;Rupar et al, 1996;Garrett et al, 1998;Johnson et al, 2002a;Lee et al, 2002;Seidahmed et al, 2005;Claerhout et al, 2018;Chen et al, 2014;Rocha et al, 2014;Zaki et al, 2016;Brumaru et al, 2017;Lee et al, 2017;Mhanni et al, 2020;Sharawat et al, 2020;Du et al, 2021). Recently, four early-onset ISOD patients have been reported in Hong Kong and Taiwan, China (Chan et al, 2002;Lee et al, 2002Lee et al, , 2017Chen et al, 2014), one early-onset patient in Chinese mainland (Du et al, 2021), and one late-onset ISOD pedigree including three patients have been reported in Chinese mainland (Tian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%